Ontogenetic Change in Male Expression of Testosterone-Responsive Genes Contributes to the Emergence of Sex-Biased Gene Expression in Anolis sagrei - Hale, Matthew D.; Robinson, Christopher D.; Cox, Christian L.; Cox, Robert M. (Frontiers in Physiology, 2022)
Sex differences in gene expression tend to increase with age across a variety of species, often coincident with the development of sexual dimorphism and maturational changes in hormone levels. However, because most transcriptome-wide characterizations of sexual divergence are framed as comparisons of sex-biased gene expression across ages, it can be difficult to determine the extent to which age-biased gene expression within each sex contributes to the emergence of sex-biased gene expression. Using RNAseq in the liver of the sexually dimorphic brown anole lizard (Anolis sagrei), we found that a pronounced increase in sex-biased gene expression with age was associated with a much greater degree of age-biased gene expression in males than in females. This pattern suggests that developmental changes in males, such as maturational increases in circulating testosterone, contribute disproportionately to the ontogenetic emergence of sex-biased gene expression. To test this hypothesis, we used four different experimental contrasts to independently characterize sets of genes whose expression differed as a function of castration and/or treatment with exogenous testosterone. We found that genes that were significantly male-biased in expression or up-regulated as males matured tended to be up-regulated by testosterone, whereas genes that were female-biased or down-regulated as males matured tended to be down-regulated by testosterone. Moreover, the first two principal components describing multivariate gene expression indicated that exogenous testosterone reversed many of the feminizing effects of castration on the liver transcriptome of maturing males. Collectively, our results suggest that developmental changes that occur in males contribute disproportionately to the emergence of sex-biased gene expression in the Anolis liver, and that many of these changes are orchestrated by androgens such as testosterone.